Carbon-coated silicon-tin composite material as well as preparation method and application thereof
By adopting a multi-layer structure carbon-covered silicon-tin composite material, the problems of low first discharge capacity and poor circulation performance of the silicon-based anode material are solved, and high energy density and excellent battery performance are achieved.
Patent Information
- Application Number
- CN202411907038.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
AI Technical Summary
The existing silicon-based anode materials have low first-time discharge capacity and poor cycle performance and rate performance, which limits the development of lithium-ion batteries in the field of high energy density.
A carbon-covered silicon-tin composite material is used to form a multi-layered carbon-covered silicon-tin composite material through a porous tin skeleton and a silicon deposited layer as the core, combining a carbon layer with a porous structure and a first cladding layer of tin nanoparticles, and a second cladding layer of a chestnut-shaped carbon layer.
The battery's first discharge specific capacity, first Coulomb efficiency and cycle capacity retention rate are significantly improved, and the overall performance of the battery is improved.
Smart Images

Figure CN119650658A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon-coated silicon-tin composite material and a preparation method and application thereof. Background Art
[0002] Over the years, the continuous development of lithium-ion battery technology has greatly improved the specific capacity, energy density and cycle life stability, allowing the battery technology to be introduced into the hybrid and electric vehicle market. The traditional graphite negative electrode has a theoretical capacity of only 372mAh / g, which limits the development of high specific capacity and high energy density in the future. At present, silicon is the most promising material to replace graphite negative electrode, with a higher theoretical capacity (about 4200mAh / g), but its huge volume expansion (over 300%) leads to lower first coulomb efficiency, poor cycle performance and rate performance. Therefore, in order to realize the high energy density demand in the future, modification of silicon materials is necessary.
[0003] Chinese patent application CN 117894968A introduces a method for preparing a doped and coated spherical silicon-carbon negative electrode material, wherein nitrogen-doped silicon-carbon powder is obtained by a solvent gel method; the powder is added to a polyacrylic acid solution and an alkali solution to obtain a template solution for ultrasonic dispersion to form a suspension, isopropanol is added to the suspension and mixed evenly, and then nitrogen-doped precursor powder is obtained after suction filtration and drying; the powder is mixed with a dopamine hydrochloride solution to obtain a precursor slurry; a composite silicon-carbon material is obtained by a spray drying method; the composite material is dispersed in a silver nitrate solution and mixed and stirred, and then a modified precursor powder is obtained after centrifugal filtration and drying; the modified powder is subjected to high-temperature oxidation treatment; then, it is subjected to secondary calcination in a nitrogen atmosphere to obtain a doped and coated spherical silicon-carbon negative electrode material; the capacity retention rate of the spherical silicon-carbon composite material at the 100th cycle is 93-95%, but its first discharge capacity is only less than 550mAh / g, which shows that the technology has limited utilization of silicon materials. Summary of the invention
[0004] The present invention solves the problem of low first discharge capacity of silicon-based negative electrode materials in the prior art, and proposes a carbon-coated silicon-tin composite material and a preparation method and application thereof. The carbon-coated silicon-tin composite material of the present invention has excellent electrical conductivity and structural stability, and a battery using the carbon-coated silicon-tin composite material has excellent capacity performance, cycle performance and rate performance.
[0005] The present invention adopts the following technical solutions to solve the above technical problems:
[0006] The present invention provides a first carbon-coated silicon-tin composite material, which comprises, from inside to outside:
[0007] A core, an annular cavity and a first coating layer; the core comprises a porous tin skeleton and a silicon deposition layer coating the outside of the porous tin skeleton; the first coating layer comprises a carbon layer with a porous structure and tin nanoparticles distributed inside the carbon layer.
[0008] Preferably, the pore size of the porous tin skeleton is 8-23 nm, for example, 16.9 nm;
[0009] Preferably, the particle size of the tin nanoparticles is 10-30 nm, for example 20.5 nm;
[0010] Preferably, the mass ratio of the first coating layer to the core is (0.5-1):(2-3.5), for example, 0.8:2.8.
[0011] The present invention provides a method for preparing a carbon-coated silicon-tin composite material, which comprises the following steps:
[0012] S1, performing vapor deposition of a silicon source on porous tin to obtain a first precursor;
[0013] S2, preparing a surfactant and an organic tin source into a sol, and mixing the sol with a phenolic compound, an aldehyde compound and a catalyst, and then mixing the sol with the first precursor, polymerizing and carbonizing the sol;
[0014] In a specific embodiment, the porous tin in step S1 is the porous tin commonly used in the art. The porous tin can be obtained from the market or homemade.
[0015] In a preferred embodiment, step S0, preparing porous tin, may be further included before step S1.
[0016] Preferably, S0 comprises the following steps: stirring, standing, washing, drying and heat treating a mixture of an inorganic tin source, a surfactant and a solvent to obtain porous tin.
[0017] In the present invention, the inorganic tin source in step S0 is an inorganic tin source conventionally used in the art. The inorganic tin source in step S0 can be one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, for example, stannous sulfate or anhydrous tin chloride.
[0018] In the present invention, the surfactant in step S0 is a surfactant commonly used in the art.
[0019] In a preferred embodiment, the surfactant in step S0 is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.
[0020] In the present invention, the solvent in step S0 is a conventional solvent in the art.
[0021] In a preferred embodiment, the solvent in step S0 is deionized water.
[0022] In the present invention, the molar ratio of the inorganic tin source to the surfactant in step S0 may be (80-95):(0.8-1.5), for example, 82:1 or 85:1.
[0023] In the present invention, the stirring time in step S0 is the time conventionally used in the art. Preferably, the stirring time in step S0 can be 10-60 minutes, for example, 20 minutes.
[0024] In the present invention, the standing time in step S0 is the time conventionally used in the art. Preferably, the standing time in step S0 can be 12-38 hours, for example, 24 hours.
[0025] In the present invention, the heat treatment time in step S0 may be 3-8 hours, for example, 4 hours.
[0026] In the present invention, the temperature of the heat treatment in step S0 may be 500-700°C, for example, 600°C or 650°C.
[0027] In the present invention, the heating rate of the heat treatment in step S0 may be 3-15° C. / min, for example, 5° C. / min.
[0028] In a specific embodiment, the vapor deposition of the silicon source in step S1 comprises the following steps:
[0029] S1-1, mixing porous tin with a circulating silicon source;
[0030] S1-2, adding a reducing agent to carry out a reduction reaction to obtain a first precursor.
[0031] In the present invention, the silicon source in step S1-1 may be one or more of tetraethoxysilane, methylsilane, ethylsilane and silane.
[0032] In the present invention, the flow rate of the silicon source in step S1-1 may be 50-100 mL / min, for example, 80 mL / min.
[0033] In the present invention, the mixing temperature in step S1-1 may be 200-400°C, for example, 300°C or 350°C.
[0034] In the present invention, the mixing time in step S1-1 may be 24-48 hours, for example, 30 hours.
[0035] In the present invention, the number of cycles in step S1-1 may be 100-300 times, for example, 180 or 220 times.
[0036] In the present invention, the mass ratio of the porous tin in step S1-1 to the reducing agent in step S1-2 may be (10-30):(1-5), for example, 15:3;
[0037] In the present invention, the reducing agent in step S1-2 is a reducing agent commonly used in the art. Preferably, the reducing agent in step S1-2 is one or more of sodium borohydride, nickel borohydride, lithium borohydride and lithium aluminum hydride.
[0038] In a preferred embodiment, before performing step S1-2, a non-reactive gas is used to purge and remove residual impurity gases, and the temperature is quickly cooled to room temperature. The non-reactive gas is a non-reactive gas conventionally used in the art, such as nitrogen, argon or helium. Preferably, the cooling rate is 20-50°C / min, for example, 30°C / min.
[0039] In the present invention, the reduction time in step S1-2 may be 2-6 hours, for example, 4 hours.
[0040] In the present invention, the reduction temperature in step S1-2 may be 40-60°C, for example, 50°C.
[0041] In a specific implementation, step S2 includes the following steps:
[0042] S2-1, stirring an aqueous solution containing a surfactant, an organic tin source, a phenolic compound, an aldehyde compound and a catalyst to obtain a sol;
[0043] S2-2, adding the first precursor and obtaining a sol through polymerization;
[0044] S2-3, after drying and carbonization, cooling is performed to obtain a first carbon-coated silicon-tin composite material.
[0045] In the present invention, the surfactant in step S2-1 is a surfactant commonly used in the art. Preferably, the surfactant in step S2-1 can be one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.
[0046] In the present invention, the organic tin source in step S2-1 can be one or more of tributylphenyltin, tetraphenyltin, phenylacetyl tributyltin and dibutyldiphenyltin.
[0047] In the present invention, the nitrogen source in step S2-1 is preferably selected from one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobis(ethylbutyronitrile) and pyrrole;
[0048] In the present invention, the carbon source in step S2-1 preferably includes a phenolic compound and an aldehyde compound; wherein the phenolic compound is preferably resorcinol; the aldehyde compound is preferably formaldehyde; preferably, the molar ratio of the phenolic compound, the aldehyde compound and the catalyst is (0.5-1.5): (500-1500): (0.007-0.03), for example, 1.2:1200:0.009;
[0049] In step S2-1, the catalyst may be one or more of sodium carbonate, sodium hydroxide and sodium citrate.
[0050] In step S2-1, the molar ratio of the surfactant, the organic tin source and the catalyst may be (0.55-0.85):(0.8-2.0):(0.007-0.03), for example, 0.65:1.3:0.009 or 0.65:1:0.009.
[0051] In a preferred embodiment, the sol in step S2-2 is a sol polymer of carbon-encapsulated silicon-deposited tin.
[0052] In the present invention, the mass ratio of the first precursor in step S2-2 to the surfactant in step S2-1 is preferably (2-3.5):(0.04-0.07), for example, 3:0.053.
[0053] In the present invention, the polymerization temperature in step S2-2 may be 80-100°C, for example, 85°C.
[0054] In the present invention, the polymerization time in step S2-2 may be 2-10 hours, for example, 8 hours.
[0055] In a preferred embodiment, the carbonization in step S2-3 is performed in a non-reactive atmosphere, and the non-reactive gas is a common non-reactive gas in the art.
[0056] In the present invention, the carbonization temperature in step S2-3 may be 500-900°C, for example, 600°C.
[0057] In the present invention, the carbonization time in step S2-3 may be 5-14 hours, for example, 9 hours.
[0058] In the present invention, the cooling rate in step S2-3 is 30-60°C / min, for example, 50°C / min.
[0059] In the present invention, in step S2-3, the core of the first carbon-coated silicon-tin composite material is a silicon-coated hollow tin structure.
[0060] The present invention provides a first carbon-coated silicon-tin composite material prepared by adopting the above-mentioned method for preparing the first carbon-coated silicon-tin composite material.
[0061] The present invention provides a second carbon-coated silicon-tin composite material, which comprises, from inside to outside, the following:
[0062] A core, an annular cavity, a first coating layer and a second coating layer; the core comprises a porous tin skeleton and a silicon deposition layer coating the outside of the porous tin skeleton; the first coating layer comprises a carbon layer with a porous structure and tin nanoparticles distributed inside the carbon layer; the second coating layer is a chestnut-shaped carbon layer;
[0063] Preferably, the pore size of the porous tin skeleton is 8-23 nm, for example, 16.9 nm;
[0064] Preferably, the particle size of the tin nanoparticles is 10-30 nm, for example 20.5 nm;
[0065] Preferably, the mass ratio of the first coating layer to the core is (0.5-1):(2-3.5), for example, 0.8:2.8;
[0066] Preferably, the mass ratio of the second coating layer to the first coating layer is (0.1-0.3):(0.5-1), for example, 0.2:0.75.
[0067] The present invention provides a method for preparing a second carbon-coated silicon-tin composite material, the preparation method comprising the following steps:
[0068] S3, mixing the dispersion of the first carbon-coated silicon-tin composite material with a nickel source, an alkali solution, and an initiator, drying, heat-treating, re-dissolving, mixing with a carbon source, drying and calcining, removing the template layer, and drying;
[0069] Preferably, the preparation method of the second carbon-coated silicon-tin composite material comprises the following steps:
[0070] S3-1, ultrasonically dispersing the first carbon-coated silicon-tin composite material in a quaternary ammonium salt aqueous solution to obtain a first carbon-coated silicon-tin composite material dispersion; adding an aqueous solution containing a nickel salt and an initiator to the first carbon-coated silicon-tin composite material dispersion, stirring, adding an alkali solution, reacting under stirring, centrifuging, and drying to obtain a composite material A;
[0071] S3-2, performing a first carbonization on the composite material A and cooling the composite material A to obtain a composite material B;
[0072] S3-3, adding the composite material B to a surfactant aqueous solution, and sequentially adding a carbon source and an initiator, reacting under stirring, and centrifuging, washing and drying to obtain a composite material C;
[0073] S3-4, performing a second carbonization on the composite material C to obtain a composite material D; the composite material D comprises a nickel layer and a carbon layer;
[0074] S3-5. The composite material D is subjected to acid treatment to remove the nickel layer, and then washed and dried to form a chestnut-shaped carbon layer.
[0075] In step S3-1, the nickel salt may be a nickel salt commonly used in the art, for example, one or more selected from nickel acetate, nickel nitrate and nickel sulfate.
[0076] In step S3-1, the initiator may be an initiator commonly used in the art, for example, one or more selected from potassium persulfate, sodium persulfate, potassium hydrogen persulfate and ammonium persulfate.
[0077] In step S3-1, in the aqueous solution containing nickel salt and initiator, the concentration of the nickel salt is preferably 6-16 mg / mL.
[0078] In step S3-1, in the aqueous solution containing nickel salt and initiator, the concentration of the initiator is preferably 1-4 mg / mL.
[0079] In step S3-1, the mass ratio of the nickel salt and the initiator to the first carbon-coated silicon-tin composite material is (0.3-0.8):(0.05-0.2):(0.3-0.8), for example, 0.4:0.15:0.5.
[0080] In step S3-1, the alkali solution may be aqueous ammonia, wherein the concentration of the aqueous ammonia may be 1-10 wt%, for example, 2 wt%, wherein the amount of the aqueous ammonia is such that the pH value of the solution is 7.
[0081] In step S3-1, the mass fraction of the ammonia water is preferably 1%-20%, for example, 1.5% or 10%. Preferably, the amount of ammonia water added is 15-25 mL.
[0082] In step S3-1, the stirring temperature is, for example, 25°C.
[0083] In step S3-1, the stirring time may be 40-60 min, for example, 55 min.
[0084] In step S3-1, the quaternary ammonium salt in the quaternary ammonium salt aqueous solution may be a quaternary ammonium salt conventionally used in the art, for example, one or more selected from hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.
[0085] In step S3-1, the mass ratio of the second precursor to the quaternary ammonium salt in the quaternary ammonium salt aqueous solution may be (0.3-0.8): (0.02-0.08).
[0086] In step S3-1, the ultrasonic dispersion time may be 40-60 min.
[0087] In step S3-1, the centrifugation is performed at room temperature, and the room temperature is 15-40°C, for example, 25°C.
[0088] In step S3-1, the centrifugation time may be 30-50 min, for example, 45 min.
[0089] In step S3-1, the centrifugal rotation speed may be 200-400 r / min, for example, 350 r / min.
[0090] In step S3-2, the first carbonization may be a carbonization treatment step conventionally used in the art; wherein the temperature of the first carbonization is preferably 350-600°C, for example 450°C. The time of the first carbonization is preferably 2-5h, for example 4h; preferably, the heating rate to the first carbonization temperature may be 1-10°C / min, for example 3°C / min.
[0091] In step S3-2, the first carbonization is preferably carried out under an inert atmosphere. The inert atmosphere preferably includes an inert gas and / or nitrogen. The inert gas can be selected from one or more of helium, neon and argon. The nitrogen is preferably high-purity nitrogen.
[0092] In step S3-2, the cooling rate may be 20-50°C / min, for example, 30°C / min.
[0093] In step S3-3, the surfactant is preferably an anionic surfactant, wherein the anionic surfactant can be selected from one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate.
[0094] In step S3-3, the concentration of the surfactant aqueous solution is preferably 12-40 mg / L, for example 32 mg / L.
[0095] In step S3-3, the mass ratio of the composite material B to the surfactant in the surfactant aqueous solution may be (1-5):(0.06-0.15), for example, 2.8:0.08.
[0096] In step S3-3, the carbon source may be pyrrole and / or pyridine.
[0097] In step S3-3, the initiator may include one or more of potassium persulfate, sodium persulfate, potassium hydrogen persulfate and ammonium persulfate.
[0098] In step S3-3, the mass ratio of the composite material B to the initiator may be 1:(2.5-7.5), for example, 1:3.4.
[0099] In step S3-3, the step of adding a heteroatom compound before adding a carbon source is also performed. Preferably, the heteroatom compound comprises one or more of a nitrogen source, a boron source and a phosphorus source. Wherein, the nitrogen source is preferably selected from one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobis(ethylbutyronitrile) and pyrrole, for example, pyrrole. The boron source is preferably selected from one or more of boric acid, triethyl borate and tripropyl borate. The phosphorus source is preferably selected from one or more of phytic acid, phosphoric acid and diammonium hydrogen phosphate.
[0100] Preferably, the step of adding the heteroatom compound further comprises stirring. Preferably, the stirring time is 40-60 min, for example, 55 min. Preferably, the stirring temperature is 0-5°C, for example, 2°C.
[0101] In step S3-3, the reaction temperature may be lower than 5°C, for example, 3°C.
[0102] In step S3-3, the reaction time is, for example, 24 h.
[0103] In step S3-3, the detergent used for washing is preferably water and / or ethanol.
[0104] In step S3-4, the second carbonization may be a carbonization treatment step conventionally used in the art, wherein the temperature of the second carbonization is preferably 550-850°C, for example 600°C, and the time of the second carbonization is preferably 3-10 h, for example 7 h.
[0105] In step S3-5, the acid treatment may be an acid treatment step used in the art. Preferably, the acid used in the acid treatment may be selected from one or more of hydrochloric acid, nitric acid and sulfuric acid. Preferably, the concentration of the acid used in the acid treatment is preferably 3-10 mol / L, for example, 5 mol / L or 8 mol / L.
[0106] In step S3-5, the washing detergent is preferably water.
[0107] The present invention provides a second carbon-coated silicon-tin composite material prepared by adopting the above-mentioned method for preparing the second carbon-coated silicon-tin composite material.
[0108] The present invention provides a third carbon-coated silicon-tin composite material, which comprises, from inside to outside:
[0109] An inner core, an annular cavity, a first coating layer, a second coating layer and a third coating layer; the inner core comprises a porous tin skeleton, and a silicon deposition layer coating the outside of the porous tin skeleton; the first coating layer comprises a carbon layer with a pore structure and tin nanoparticles distributed inside the carbon layer; the second coating layer is a chestnut-shaped carbon layer; the third coating layer is a carbon layer, and there is a gap formed between the third coating layer and the second coating layer formed between adjacent chestnut-shaped carbons;
[0110] Preferably, the pore size of the porous tin skeleton is 8-23 nm, for example, 16.9 nm;
[0111] Preferably, the particle size of the tin nanoparticles is 10-30 nm, for example 20.5 nm;
[0112] Preferably, the mass ratio of the first coating layer to the core is (0.5-1):(2-3.5), for example, 0.8:2.8;
[0113] Preferably, the mass ratio of the second coating layer to the first coating layer is (0.1-0.3):(0.5-1), for example, 0.2:0.75;
[0114] Preferably, the mass ratio of the third coating layer to the second coating layer is (0.7-1):(0.1-0.3), for example, 0.8:0.2.
[0115] The present invention provides a method for preparing a third carbon-coated silicon-tin composite material, the preparation method comprising the following steps: S4, mixing a phenolic compound, an aldehyde compound and a catalyst, and then mixing the mixture with the second carbon-coated silicon-tin composite material, performing a polymerization reaction, and carbonizing.
[0116] Preferably, the preparation method of the third carbon-coated silicon-tin composite material comprises the following steps:
[0117] S4-1, adding a phenolic compound, an aldehyde compound and a catalyst into water and mixing to obtain a premix, and adding a second carbon-coated silicon-tin composite material;
[0118] S4-2, polymerization, drying and carbonization.
[0119] In the present invention, the premix in step S4-1 may further include a surfactant and / or graphene and / or a nitrogen source. More preferably, the premix further includes a surfactant, graphene and a nitrogen source, and the molar ratio of the surfactant, graphene, nitrogen source and catalyst is (0.55-0.85) mmol: (0.3-1) mmol: (0.01-0.09) mmol: (0.007-0.03) mmol, for example 0.65 mmol: 0.9 mmol: 0.03 mmol: 0.008 mmol.
[0120] In the present invention, the phenolic compound in step S4-1 may be resorcinol.
[0121] In the present invention, the aldehyde compound in step S4-1 may be formaldehyde.
[0122] In a preferred embodiment, the molar ratio of the phenolic compound to the aldehyde compound is (0.5-1.5) mol: (500-1500) mol, for example, 1 mmol: 1000 mmol.
[0123] In a preferred embodiment, the mass ratio of the aldehyde compound to the second carbon-coated silicon-tin composite material is (15-45):(3-4), for example, 30:3.2.
[0124] In the present invention, the alkali in step S4-1 can be one or more of sodium carbonate, sodium hydroxide and sodium citrate.
[0125] In the present invention, the polymerization time in step S4-2 may be 2-10 hours, for example, 5 hours.
[0126] In the present invention, the polymerization temperature in step S4-2 may be 80-100°C, for example, 85°C.
[0127] In the present invention, the carbonization time in step S4-2 may be 5-14 hours, for example, 7 hours.
[0128] In the present invention, the carbonization temperature in step S4-2 may be 500-900°C, for example, 600°C.
[0129] The present invention provides a third carbon-coated silicon-tin composite material prepared by adopting the preparation method of the third carbon-coated silicon-tin composite material.
[0130] The present invention provides use of the first carbon-coated silicon-tin composite material, the second carbon-coated silicon-tin composite material and the third carbon-coated silicon-tin composite material as electrode materials in a battery.
[0131] Wherein, the electrode material is preferably a negative electrode material.
[0132] In the present invention, all drying steps are drying methods conventionally used in the art. Preferably, all drying steps can be carried out in one of the following three ways:
[0133] (1) Freeze drying, wherein the freeze drying temperature may be -30°C to -80°C, and the drying time may be 3-7 hours;
[0134] (2) CO2 supercritical drying, wherein the CO2 supercritical drying temperature may be 10-40°C, the pressure may be 10-15 kPa, and the drying time may be 1-3 hours;
[0135] (3) Vacuum drying, wherein the vacuum drying temperature may be 60-90°C, such as 80°C, and the drying time may be 4-20h.
[0136] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0137] The reagents and raw materials used in the present invention are commercially available.
[0138] The positive and progressive effects of the present invention are:
[0139] (1) The carbon-coated silicon-tin composite material obtained by the preparation method of the present invention has a hollow carbon layer and a hollow core structure. The modified structure can not only fully utilize the advantages of silicon materials, but also improve their defects such as low electrical conductivity and huge volume expansion. The battery using the carbon-coated silicon-tin composite material has an initial discharge specific capacity of 1409.9 mAh / g, an initial coulombic efficiency of more than 89.1%, and a capacity retention rate of more than 87.6% after 100 cycles at a rate of 0.1C.
[0140] (2) In a preferred embodiment, a multi-layer carbon-coated three-dimensional structure with a graphene layer and a chestnut-shaped carbon layer is added to further improve the low conductivity and huge volume expansion defects of silicon materials. Among them, the multi-layer carbon layer can play the role of multi-layer buffering the volume expansion of the silicon-tin material. At the same time, this multi-layer hollow structure increases the lithium ion transmission pathway to obtain better rate and cycle performance, so that the battery using the carbon-coated silicon-tin composite material has an initial discharge specific capacity of 1409.9mAh / g, an initial coulomb efficiency of more than 93.7%, and a capacity retention rate of more than 92.9% for 100 cycles at a rate of 0.1C. BRIEF DESCRIPTION OF THE DRAWINGS
[0141] Figure 1The schematic diagram of the structure of the carbon-coated silicon-tin composite material prepared in Example 1 of the present invention. 1 is the core, 11 is the pore, 12 is the porous tin skeleton, 13 is the silicon deposition layer; 2 is the annular cavity; 3 is the first coating layer, 31 is the carbon layer with a porous structure, 32 is the tin nanoparticles; 4 is the second coating layer, 5 is the pore, and 6 is the third coating layer.
[0142] Figure 2 This is a rate performance diagram of the carbon-coated silicon-tin composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0143] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0144] Anhydrous tin chloride, analytical grade, was purchased from Wuxi WuXi AppTec Pharmaceutical Development Co., Ltd.;
[0145] Stannous sulfate, analytical grade, was purchased from Wuxi WuXi AppTec Pharmaceutical Development Co., Ltd.;
[0146] Octadecyltrimethylammonium chloride, analytical grade, was purchased from Shanghai Aoxing Pharmaceutical Technology Equipment Co., Ltd.;
[0147] Hexadecyltrimethylammonium bromide, analytical grade, was purchased from Shanghai Aoxing Pharmaceutical Technology Equipment Co., Ltd.;
[0148] Sodium borohydride, purchased from Liaoning Dongxiang Chemical Co., Ltd.;
[0149] Resorcinol and formaldehyde, analytical grade, were purchased from Sinopharm Group;
[0150] Quaternary ammonium salts, analytical grade, were purchased from Hangzhou Jessica Chemical Co., Ltd.;
[0151] Pyridine and pyrrole, analytical grade, were purchased from Wanhua Chemical;
[0152] Hydrochloric acid, analytical grade, was purchased from Sinopharm Group;
[0153] Nickel acetate, analytical grade, was purchased from Sinopharm Group;
[0154] Potassium persulfate, analytical grade, was purchased from Wanhua Chemical.
[0155] Example 1
[0156] S0. Preparation of porous tin
[0157] Anhydrous tin chloride (82 mmol) was added to deionized water (135 mL) and stirred until completely dissolved. The mixture was stirred for 20 min to ensure complete dissolution of anhydrous tin chloride. Then 1 mmol hexadecyltrimethylammonium bromide was added, stirred evenly and allowed to stand for 24 h to stabilize the formation of the sol, then rinsed repeatedly with water and ethanol, dried at 85°C under vacuum for 24 h, and then heat treated at 650°C (heating rate of 5°C / min) for 4 h. Porous tin was obtained.
[0158] S1. Silicon deposition
[0159] S1-1. 15 g of porous tin was used as a base template and sent into a Beneq TFS 200 atomic layer deposition (ALD) device. Tetraethoxysilane gas was introduced at a flow rate of 80 mL / min at a working temperature of 300° C. for 30 hours and 180 cycles.
[0160] S1-2. After stopping the cycle, use nitrogen to purge to remove residual impurity gases, quickly cool down to room temperature at a cooling rate of 30°C / min, and add 3g of sodium borohydride for reduction (reduction time is 4h, reduction temperature is 50°C), and the first precursor can be obtained.
[0161] S2. Obtaining the first carbon-coated silicon-tin composite material
[0162] S2-1, 0.65mmol of dialkyldimethylammonium chloride and 1.3mmol of tributylphenyltin were mixed, and ultrasonically dispersed for 45min to make them uniformly distributed in deionized water (8mol), and spherical micelles were formed and fixed. Then, a mixture of 0.03mmol of nitrogen source, resorcinol (1.2mmol), formaldehyde (1.2mol) and sodium carbonate (0.009mmol) was added, and stirred continuously to obtain a sol.
[0163] S2-2, adding 3 g of the first precursor to obtain a stable core-shell colloid, and then polymerizing the core-shell colloid at 85° C. for 8 h to obtain a sol.
[0164] S2-3. After drying, heat treatment is performed at 600° C. for 9 h under nitrogen to carbonize the gel polymer, and rapid cooling is performed at a cooling rate of 50° C. / min to obtain a first carbon-coated silicon-tin composite material.
[0165] S3. Obtaining the second carbon-coated silicon-tin composite material
[0166] S3-1. Add 0.5g of the first carbon-coated silicon-tin composite material to 50 mL of deionized water dissolved with 0.05g of hexadecyltrimethylammonium bromide, stir, and ultrasonically treat for 55 minutes to make the first carbon-coated silicon-tin composite material well distributed and preserved. Dissolve 0.4g of nickel acetate and 0.15g of potassium persulfate in another 50 mL of distilled water. After complete dissolution, slowly add to the dispersion of the first carbon-coated silicon-tin composite material. After stirring for 55 minutes, add 18 mL of 2wt% ammonia water. Stir again at 25°C in an oil bath, and finally, collect the product after centrifugation at room temperature for 45 minutes (speed of 350r / min), and vacuum dry at 85°C for 30 hours to obtain composite material A.
[0167] S3-2, the composite material A was then heated at 400°C at a rate of 3°C / min in an inert atmosphere, and after being kept at a constant temperature for 3.5 hours, it was rapidly cooled at a cooling rate of 30°C / min to prepare a core-shell chestnut-shaped structure composite material B.
[0168] S3-3, dissolve 8 mg of sodium dodecylbenzene sulfonate in 250 mL of deionized water. Add 0.28 g of composite material B and stir for 55 min; put 0.25 mL of pyrrole into an ice bath at 2°C and stir for 55 min. At the same time, dissolve 0.34 g of potassium persulfate in 40 mL of distilled water. After complete dissolution, add it to the pyrrole mixed solution and stir at a reaction temperature of 3°C for 24 h. At the end of the reaction, collect the product by centrifugation, wash with distilled water and ethanol in turn to remove impurities, and vacuum dry at 85°C for 28 h to obtain composite material C.
[0169] S3-4. Finally, the composite material C was calcined at 600° C. for 7 h in an argon atmosphere and then rapidly cooled to obtain a composite material D coated with a nitrogen-doped carbon layer.
[0170] S3-5, remove the nickel oxide layer in the composite material D with 5 mol / l hydrochloric acid, wash the material with deionized water to neutrality, and finally vacuum dry at 85° C. for 28 h to obtain a second carbon-coated silicon-tin composite material.
[0171] S4. Obtaining the third carbon-coated silicon-tin composite material
[0172] S4-1, 0.65mmol of dialkyldimethylammonium chloride was mixed with 0.9mmol of graphene, and ultrasonically dispersed for 45min to make it uniformly distributed in deionized water (8 mol), and spherical micelles were formed and fixed. A mixture of 0.03mmol of nitrogen source, resorcinol (1mmol), formaldehyde (1 mol) and sodium carbonate (0.008 mmol) was added, and stirred continuously to obtain a surface-stabilized sol. Subsequently, 3.2g of a second carbon-coated silicon-tin composite material was added to obtain a surfactant-stabilized core-shell colloid.
[0173] S4-2, polymerizing the core-shell colloid at 85°C for 5 hours, drying it, and then heat treating it at 600°C for 7 hours under nitrogen.
[0174] The structural diagram of the obtained product is shown in Figure 1 As shown, it includes from the inside to the outside: a core 1, an annular cavity 2, a first coating layer 3, a second coating layer 4 and a third coating layer 6; the core includes a porous tin skeleton 12 and a silicon deposition layer 13 coated on the outside of the porous tin skeleton; the first coating layer includes a carbon layer 31 with a pore structure and tin nanoparticles 32 distributed inside the carbon layer; the second coating layer 4 is a chestnut-shaped carbon layer; the third coating layer 6 is a carbon layer, and there is a gap 5 formed between the third coating layer 6 and the second coating layer 4. Among them, the pore size of the porous tin skeleton is 16.9 nm, the particle size of the tin nanoparticles is 20.5 nm, the mass ratio of the first coating layer to the core is 0.8:2.8, the mass ratio of the second coating layer to the first coating layer is 0.2:0.75, and the mass ratio of the third coating layer to the second coating layer is 0.8:0.2.
[0175] Example 2
[0176] The difference from Example 1 is that the inorganic tin source in step S0 is stannous sulfate, and the other conditions are exactly the same as those in Example 1.
[0177] Example 3
[0178] The difference from Example 1 is that 85 mmol of anhydrous tin chloride is added in step S0, and the other conditions are exactly the same as those in Example 1.
[0179] Example 4
[0180] The difference from Example 1 is that the heat treatment temperature in step S0 is 600° C., and the other conditions are exactly the same as those in Example 1.
[0181] Example 5
[0182] The difference from Example 1 is that the working temperature in step S1 is 350° C., and the other conditions are exactly the same as those in Example 1.
[0183] Example 6
[0184] The difference from Example 1 is that the number of cycles in step S1 is 220 times, and the other conditions are exactly the same as those in Example 1.
[0185] Example 7
[0186] The difference from Example 1 is that the surfactant in steps S2 and S4 is octadecyltrimethylammonium chloride, and the other conditions are exactly the same as in Example 1.
[0187] Example 8
[0188] The difference from Example 1 is that 1 mmol of tributylphenyltin is added in step S2-1, and the other conditions are exactly the same as those in Example 1.
[0189] Example 9
[0190] The difference from Example 1 is that 2.5 g of the first precursor is added in step S2-2, and the other conditions are exactly the same as in Example 1.
[0191] Example 10
[0192] The difference from Example 1 is that the heat treatment temperature in step S2-3 is 700°C, and the other conditions are exactly the same as in Example 1.
[0193] Embodiment 11
[0194] The difference from Example 1 is that no nitrogen source is added in step S4-1, and the other conditions are exactly the same as in Example 1.
[0195] Example 12
[0196] The difference from Example 1 is that step S3 is not performed (ie, the chestnut-like structure is not introduced, and the product of step S2 is directly applied to step S4-1), and the other conditions are exactly the same as in Example 1.
[0197] Example 13
[0198] The difference from Example 1 is that 0.6 mmol of graphene is added in step S4-1, and the other conditions are exactly the same as those in Example 1.
[0199] Embodiment 14
[0200] The difference from Example 1 is that 3.8 g of the second carbon-coated silicon-tin composite material is added in step S4-1, and the other conditions are exactly the same as in Example 1.
[0201] Embodiment 15
[0202] The difference from Example 1 is that graphene is not added in step S4-1, and the other conditions are exactly the same as those in Example 1.
[0203] Example 16
[0204] The difference from Example 1 is that step S4 is not performed, and the other conditions are exactly the same as those in Example 1.
[0205] Embodiment 17
[0206] The difference from Example 1 is that steps S3-S4 are not performed, and the other conditions are exactly the same as those in Example 1.
[0207] Embodiment 18
[0208] The difference from Example 1 is that no nitrogen source is added in steps S2-1 and S4-1.
[0209] Comparative Example 1
[0210] Pure silicon powder is used directly without any treatment.
[0211] Comparative Example 2
[0212] The difference from the first embodiment is that only step S0 is performed.
[0213] Comparative Example 3
[0214] The difference from Embodiment 1 is that only steps S0-S1 are performed.
[0215] Comparative Example 4
[0216] The difference from Example 1 is that step S2 is not performed (the product of step S1 is directly applied to step S3), and the other conditions are exactly the same as those of Example 1.
[0217] Effect embodiment 1:
[0218] Physical and chemical properties test:
[0219] XRF was used to test the element content (silicon, tin, carbon, oxygen, nitrogen content) in the carbon-coated silicon-tin composite material prepared by the present invention. The test method was microwave digestion, and Examples 1-18 and Comparative Examples 1-4 were pre-treated: 2±0.05g of stearic acid and 6±0.5g of the sample to be tested were mixed and ground, then pressed into tablets, and then tested in an Avio™ 200 device; test conditions: air pressure greater than 2MPa.
[0220] The D50 of the carbon-coated silicon-tin composite materials prepared in the examples and comparative examples was tested using a Malvern particle size tester.
[0221] Conductivity model Measured at room temperature.
[0222] The pore size is measured by POROLUX Cito pore sizer.
[0223] The charge transfer resistance was measured by electrochemical impedance spectroscopy (compacted density 1.65 g / cm 3 )get.
[0224] Examples 1-18 and Comparative Examples 1-4 were tested according to the above test method, and the results are shown in Table 1.
[0225] Table 1 Physical and chemical performance parameters
[0226]
[0227] Effect embodiment 2:
[0228] Lithium-ion button cell battery testing:
[0229] The preparation method of the button cell used for testing the electrochemical performance is as follows: the battery negative electrode material prepared in the embodiment and the comparative example is mixed evenly with the conductive agent (KS-6), CMC, and SBR according to 95.5:1.5:1.5:1.5, and applied on the copper foil. The compaction density is 1.60g / cm 3 , vacuum dried as the negative electrode, lithium metal as the counter electrode, the electrolyte using 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, the separator is PE / PP / PE composite film, and assembled into a button battery.
[0230] The test conditions are: rate charging and discharging at a rate of 0.1C-3C, and the charging voltage limit is 0.005-2V.
[0231] According to the above test method, the first discharge specific capacity, first efficiency, and 100 and 200 cycle capacities at 0.1C rate of Examples 1-18 and Comparative Examples 1-4 were tested, and the test results are shown in Table 2. Among them, the test results of the carbon-coated silicon-tin composite material obtained in Example 1 at different rates (5 cycles at the same rate) are shown in Table 2. Figure 2 As shown by Figure 2 It can be seen that the carbon-coated silicon-tin composite material obtained in Example 1 can still achieve performance close to that at the initial rate after high-rate discharge when restored to the initial rate, proving that the design of multi-layer carbon coating and porous core can not only alleviate the defect of volume expansion of silicon-tin material, but also obtain excellent rate performance.
[0232] Table 2 Electrochemical performance
[0233]
[0234] Compared with comparative examples 1-4, the physical and chemical properties and electrochemical properties of embodiments 1-18 are better. It can be seen that the carbon-coated silicon-tin composite material obtained by the preparation method of the present invention has a hollow carbon layer and a hollow core structure. This structure can not only fully utilize the advantages of silicon materials, but also improve its defects such as low electrical conductivity and huge volume expansion.
[0235] Compared with Example 15, Example 1 has better cycle stability because the addition of graphene can enhance the mechanical properties of the phenolic resin polymerized carbon layer, further increase its conductivity, and reduce the impact on capacity.
[0236] Compared with Example 16, Example 1 has better first effect and cycle stability. This may be because if the outer layer is only a chestnut-shaped structure, due to its unique pore structure, a large amount of lithium will be consumed later, reducing the coulombic efficiency and stability. The coating of the graphene layer can overcome these defects.
[0237] Compared with Example 17, Example 1 has better first effect and cycle stability. This may be because the multi-layer hollow structure forms a gap network, which is more conducive to the transmission of electrons, and the multi-layer carbon coating layer can better buffer the volume expansion of the silicon-tin material.
[0238] Compared with Examples 1-18, Comparative Example 3 has lower conductivity and poorer first efficiency and cycle stability. This may be because the improvement effect on the volume expansion of silicon materials and tin materials is limited by simply relying on silicon deposition on the porous tin surface, which still leads to poor first efficiency and cycle performance.
[0239] Compared with Examples 1-18, Comparative Example 4 has poor first effect and cycle stability. This may be because the chestnut-like carbon layer is directly coated on the surface of the silicon-deposited porous tin. Although the chestnut-like carbon layer and the porous skeleton work synergistically to partially alleviate the volume expansion of silicon and tin, due to the developed void structure of the chestnut-like carbon, its first effect and cycle performance are worse than those of the examples, but better than those of Comparative Example 3.
Claims
1. A first carbon-coated silicon-tin composite material, characterized in that: The first carbon-coated silicon-tin composite material comprises, from inside to outside: A core, an annular cavity and a first coating layer; the core comprises a porous tin skeleton and a silicon deposition layer coating the outside of the porous tin skeleton; the first coating layer comprises a carbon layer with a porous structure and tin nanoparticles distributed inside the carbon layer; Preferably, the pore size of the porous tin skeleton is 8-23 nm, for example, 16.9 nm; Preferably, the particle size of the tin nanoparticles is 10-30 nm, for example 20.5 nm; Preferably, the mass ratio of the first coating layer to the core is (0.5-1):(2-3.5), for example, 0.8:2.
8.
2. A method for preparing a first carbon-coated silicon-tin composite material, characterized in that: The preparation method comprises the following steps: S1, performing vapor deposition of a silicon source on porous tin to obtain a first precursor; S2, preparing a surfactant and an organic tin source into a sol, and mixing the sol with a phenolic compound, an aldehyde compound and a catalyst, and then mixing the sol with the first precursor, polymerizing and carbonizing the sol; Preferably, step S0 is included before step S1; preferably, S0 includes the following steps: stirring, standing, washing, drying and heat treating a mixture of an inorganic tin source, a surfactant and a solvent to obtain porous tin; more preferably, the inorganic tin source is one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, for example, stannous sulfate or anhydrous tin chloride; more preferably, the molar ratio of the inorganic tin source to the surfactant is (80-95): (0.8-1.5), for example, 82:1 or 85:1; more preferably, the temperature of the heat treatment is 500-700°C, for example, 600°C or 650°C; Preferably, the vapor deposition of the silicon source in step S1 comprises the following steps: S1-1, mixing porous tin with a circulating silicon source; Preferably, the mixing temperature is 200-400°C, for example, 300°C or 350°C; preferably, the mixing time is 24-48h, for example, 30h; preferably, the number of cycles is 100-300 times, for example, 180 or 220 times; preferably, the silicon source is one or more of tetraethoxysilane, methylsilane, ethylsilane and silane; S1-2, adding a reducing agent to carry out a reduction reaction to obtain a first precursor; Preferably, the reducing agent is one or more of sodium borohydride, nickel borohydride, lithium borohydride and lithium aluminum hydride; preferably, the reduction time is 2-6 hours, for example, 4 hours; preferably, the reduction temperature is 40-60°C, for example, 50°C; preferably, the mass ratio of the porous tin in step S1-1 to the reducing agent in step S1-2 is (10-30): (1-5), for example, 15:3; Preferably, step S2 comprises the following steps: S2-1, stirring an aqueous solution containing a surfactant, an organic tin source, a phenolic compound, an aldehyde compound and a catalyst to obtain a sol; Preferably, the molar ratio of the surfactant, the organic tin source and the catalyst is (0.55-0.85):(0.8-2.0):(0.007-0.03), for example, 0.65:1.3:0.009 or 0.65:1:0.009; Preferably, a nitrogen source is added before stirring; more preferably, the nitrogen source is one or more of melamine, polyimide and urea; Preferably, the surfactant is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide; preferably, the organic tin source is one or more of tributylphenyltin, tetraphenyltin, phenylacetyltributyltin and dibutyldiphenyltin; preferably, the phenolic compound is resorcinol, and the aldehyde compound is formaldehyde; more preferably, the molar ratio of the phenolic compound, the aldehyde compound and the catalyst is (0.5-1.5): (500-1500): (0.007-0.03), for example, 1.2:1200:0.009; preferably, the catalyst is a base; more preferably, the base is one or more of sodium carbonate, sodium hydroxide and sodium citrate; S2-2, adding the first precursor and obtaining a sol through polymerization; Preferably, the mass ratio of the first precursor to the surfactant in step S2-1 is preferably (2-3.5): (0.04-0.07), for example, 3:0.053; preferably, the polymerization temperature is 80-100°C, for example, 85°C; preferably, the polymerization time is 2-10h, for example, 8h; S2-3, drying, carbonizing and then cooling to obtain a first carbon-coated silicon-tin composite material; Preferably, the carbonization temperature is 500-900° C., for example, 600° C.; the carbonization time is 5-14 h, for example, 9 h.
3. A first carbon-coated silicon-tin composite material prepared by the preparation method of the first carbon-coated silicon-tin composite material according to claim 2.
4. A second carbon-coated silicon-tin composite material, characterized in that: The second carbon-coated silicon-tin composite material comprises, from inside to outside: A core, an annular cavity, a first coating layer and a second coating layer; the core comprises a porous tin skeleton and a silicon deposition layer coating the outside of the porous tin skeleton; the first coating layer comprises a carbon layer with a porous structure and tin nanoparticles distributed inside the carbon layer; the second coating layer is a chestnut-shaped carbon layer; Preferably, the pore size of the porous tin skeleton is 8-23 nm, for example, 16.9 nm; Preferably, the particle size of the tin nanoparticles is 10-30 nm, for example 20.5 nm; Preferably, the mass ratio of the first coating layer to the core is (0.5-1):(2-3.5), for example, 0.8:2.8; Preferably, the mass ratio of the second coating layer to the first coating layer is (0.1-0.3):(0.5-1), for example, 0.2:0.
75.
5. A method for preparing a second carbon-coated silicon-tin composite material, characterized in that: The preparation method comprises the following steps: S3, mixing the dispersion of the first carbon-coated silicon-tin composite material according to claim 3 with a nickel source, an alkali solution, and an initiator, drying, heat-treating, re-dissolving, mixing with a carbon source, drying and calcining, removing the template layer, and drying; Preferably, the preparation method of the second carbon-coated silicon-tin composite material comprises the following steps: S3-1, ultrasonically dispersing the first carbon-coated silicon-tin composite material of claim 3 in a quaternary ammonium salt aqueous solution to obtain a first carbon-coated silicon-tin composite material dispersion; adding an aqueous solution containing a nickel salt and an initiator to the first carbon-coated silicon-tin composite material dispersion, stirring, adding an alkali solution, reacting under stirring, centrifuging, and drying to obtain a composite material A; Preferably, the quaternary ammonium salt is selected from one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide; preferably, the nickel salt is selected from one or more of nickel acetate, nickel nitrate and nickel sulfate; preferably, the initiator is selected from one or more of potassium persulfate, sodium persulfate, potassium hydrogen persulfate and ammonium persulfate; preferably, the mass ratio of the quaternary ammonium salt in the first carbon-coated silicon-tin composite material and the quaternary ammonium salt aqueous solution is (0.3-0.8): (0.02-0.08); preferably, the mass ratio of the nickel salt and the initiator to the first carbon-coated silicon-tin composite material is (0.3-0.8): (0.05-0.2): (0.3-0.8), for example, 0.4:0.15:0.5; preferably, the alkali solution is ammonia water; more preferably, the concentration of the ammonia water is 1-10 wt%, for example, 2 wt%; more preferably, the amount of ammonia water is added dropwise until the pH value of the solution reaches 7; S3-2, performing a first carbonization on the composite material A and cooling the composite material A to obtain a composite material B; Preferably, the temperature of the heat treatment is 350-600°C, for example, 450°C; preferably, the time of the heat treatment is 2-5h, for example, 4h; preferably, the heating rate to the temperature of the heat treatment is 1-10°C / min, for example, 3°C / min; S3-3, adding the composite material B to a surfactant aqueous solution, and sequentially adding a carbon source and an initiator, reacting under stirring, and centrifuging, washing and drying to obtain a composite material C; Preferably, the carbon source is pyrrole and / or pyridine; preferably, the surfactant is an anionic surfactant; more preferably, the anionic surfactant is selected from one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate; preferably, the mass ratio of the composite material B to the surfactant in the surfactant aqueous solution is (1-5): (0.06-0.15), for example, 2.8:0.08; preferably, the initiator includes one or more of potassium persulfate, sodium persulfate, potassium hydrogen persulfate and ammonium persulfate; preferably, the mass ratio of the composite material B to the initiator is 1: (2.5-7.5), for example, 1:3.4; preferably, the reaction temperature is lower than 5°C, for example, 3°C; preferably, the reaction time is, for example, 24 h; S3-4, performing a second carbonization on the composite material C to obtain a composite material D; the composite material D comprises a nickel layer and a carbon layer; Preferably, the temperature of the second carbonization is 550-850°C, for example, 600°C; preferably, the time of the second carbonization is 3-10 h, for example, 7 h; S3-5, treating the composite material D with acid to remove the nickel layer, washing, and drying to form a chestnut-shaped carbon layer; Preferably, the acid used in the acid treatment is selected from one or more of hydrochloric acid, nitric acid and sulfuric acid; preferably, the concentration of the acid used in the acid treatment is 3-10 mol / L, for example, 5 mol / L or 8 mol / L; preferably, the washing detergent is water. 6 . A second carbon-coated silicon-tin composite material prepared by the method for preparing the second carbon-coated silicon-tin composite material according to claim 5 .
7. A third carbon-coated silicon-tin composite material, characterized in that: The third carbon-coated silicon-tin composite material comprises, from inside to outside: An inner core, an annular cavity, a first coating layer, a second coating layer and a third coating layer; the inner core comprises a porous tin skeleton, and a silicon deposition layer coating the outside of the porous tin skeleton; the first coating layer comprises a carbon layer with a pore structure and tin nanoparticles distributed inside the carbon layer; the second coating layer is a chestnut-shaped carbon layer; the third coating layer is a carbon layer, and there is a gap formed between the third coating layer and the second coating layer formed between adjacent chestnut-shaped carbons; Preferably, the pore size of the porous tin skeleton is 8-23 nm, for example, 16.9 nm; Preferably, the particle size of the tin nanoparticles is 10-30 nm, for example 20.5 nm; Preferably, the mass ratio of the first coating layer to the core is (0.5-1):(2-3.5), for example, 0.8:2.8; Preferably, the mass ratio of the second coating layer to the first coating layer is (0.1-0.3):(0.5-1), for example, 0.2:0.75; Preferably, the mass ratio of the third coating layer to the second coating layer is (0.7-1):(0.1-0.3), for example, 0.8:0.
2.
8. A method for preparing a third carbon-coated silicon-tin composite material, characterized in that: The preparation method comprises the following steps: S4, mixing a phenolic compound, an aldehyde compound and a catalyst, and then mixing the mixture with the second carbon-coated silicon-tin composite material according to claim 6, polymerizing and carbonizing the mixture; Preferably, the preparation method of the third carbon-coated silicon-tin composite material comprises the following steps: S4-1, adding a phenolic compound, an aldehyde compound and a catalyst into water and mixing to obtain a premix, and adding a second carbon-coated silicon-tin composite material; preferably, the premix further comprises one or more of a surfactant, graphene and a nitrogen source; more preferably, the premix further comprises a surfactant, graphene and a nitrogen source; further preferably, the molar ratio of the surfactant, graphene, nitrogen source and catalyst is (0.55-0.85) mmol: (0.3-1) mmol: (0.01-0.09) mmol: (0.007-0.03) mmol, for example, 0.65 mmol: 0.9 mmol: 0.03 mmol: 0.008 mmol; preferably, the phenolic compound is preferably resorcinol; more preferably, the aldehyde compound is preferably formaldehyde; more preferably, the molar ratio of the phenolic compound to the aldehyde compound is (0.5-1.5) mmol: (500-1500) mmol, for example, 1 mmol: 1000 mmol; more preferably, the mass ratio of the aldehyde compound to the second carbon-coated silicon-tin composite material is (15-45): (3-4), for example 30:3.2; preferably, the catalyst is a base; more preferably, the base is one or more of sodium carbonate, sodium hydroxide and sodium citrate; S4-2, polymerization, drying, and carbonization; Preferably, the polymerization time is 2-10h, for example 5h; preferably, the polymerization temperature is 80-100°C, for example 85°C; preferably, the carbonization time is 5-14h, for example 7h; preferably, the carbonization temperature is 500-900°C, for example 600°C. 9 . A third carbon-coated silicon-tin composite material prepared by the method for preparing the third carbon-coated silicon-tin composite material according to claim 8 .
10. Use of the first carbon-coated silicon-tin composite material as claimed in claim 1 or 3, the second carbon-coated silicon-tin composite material as claimed in claim 4 or 6, and the third carbon-coated silicon-tin composite material as claimed in claim 7 or 9 as electrode materials in a battery.
Citation Information
Patent Citations
Doped and coated spherical silicon carbon negative electrode material as well as preparation method and application thereof
CN117894968A